顾及三维拓扑的地下工井设施建模方法 (2022)
本发明提供了顾及三维拓扑的地下工井设施建模方法，步骤包括：点云精简；提取出工井点云主轴；将原始点云旋转，使得原始点云沿着主轴方向正立与三维空间中；构建三角面片实现工井模型的简易化建模步骤包括：a)工井顶面点云提取并进行平面拟合；b)工井底面点云提取并进行平面拟合；c)依据顶面边界线、底面边界线和顶面和底面之间的高度构建三角面片以进行贴合点云数据的简易化建模；工井模型部件构建。本发明能够适应多种点云类型，算法适应性强；本发明模型贴合实际点云，构建的模型质量好；本发明对比常用的曲面重建算法本发明构建模型速度快，实用性较强本发明实现内部管线与外部点云的有机统一，很好的满足实际场景的重现。 The invention provides a three-dimensional topology-considered underground working well facility modeling method. The method comprises the following steps of: carrying out point cloud simplification;extracting a main shaft of a point cloud of a working well; rotating an original point cloud to ensure that the original point cloud stands in a three-dimensional space along the direction of the mainshaft; constructing a triangular patch to realize simple modeling of a working well model: a) extracting a point cloud on the top surface of the working well and carrying out plane fitting, b) extracting a point cloud on the bottom surface of the working well and carrying out plane fitting, c) constructing the triangular patch a